“Avalia CAPS”: a construção e a validação de um instrumento de avaliação dos CAPS (Centro de Atenção Psicossocial) – versão usuários - Machado, Pâmela de Freitas Machado (2020)
Various national and international studies highlight the importance of evaluation and monitoring to the qualification of mental health care. In Brazil, qualitative and quantitative researches address the advances and challenges regarding the realization of the psychosocial care approach/model. In this context, the present study aimed to evaluate, through the users’ perspective, how the guidelines of the mental health policy are implemented as care strategies on the CAPS’ (Centros de Atenção Psicossocial/Psychosocial Attention Centers) routine. This study counted on a sequential mixed method research, including both qualitative and quantitative procedures, instrumented in two different studies. The first one aimed to investigate, qualitatively, through decrees and orders, how the different propositions of the mental health policy are translated into actions and care strategies on CAPS’ work according to the key informants’ interviews. The participants, as key informants, were CAPS’ users who had a significant storyline in psychological monitoring in the substitute services. The key informants contributed to the making of the items and dimensions of the quantitative instrument. The interviews were recorded, transcribed, and subjected to Spink's meanings and significations analysis. The resulting categories advocated four concepts of the field of mental health care: integrality, intersectionality, autonomy and protagonism. The data of the first study formed the instrument’s constructs to the CAPS’ evaluation. It also came to substantiate the content, semantics, and language of the items of the scale. In the second study, the construction and psychometric validity of the instrument were carried out, investigating, through the users point of view, how the concepts of integrality, intersectionality, autonomy and protagonism are put into practice on the CAPS’ routine. The scale was applied in different CAPS of two cities of Rio Grande do Sul. The instrument was called “Avalia CAPS”. To enable interviewers to apply the test along with participants, a capacitation was considered. As suggested by Pasquali (2003), the study counted with 351 users for an instrument with 35 items. Regarding the validity statistical analysis, the Exploratory Factor Analysis method was applied with the means of verifying the variability of the instrument. The adequacy of the sample was calculated through the factor analysis and the Kaiser-Meyer-Olkin (KMO) index. Finally, a convergence analysis was made, considering Pearson's correlation coefficient, between the instrument “Avalia CAPS” and the “SATIS-BR”. The goal was to find a correlation between the two scales. The instrument reached a KMO of 0.79, indicating suitability of the correlation matrix. The parallel analysis of data estimated a model containing 11 factors with 54.3% of explained variation. Nonetheless, the instrument was refined by using the scree plot method, which resulted in 8 factors. The convergence analysis with the “SATIS BR” scale made it possible to identify a significant correlation between the instruments. The instrument has a considerable validity rate, a circumstance which highlights its relevance to the health care evaluation field. Therefore, the studies assembled to form the present thesis evinced that the “Avalia CAPS”, since its initial project, was a challenging process, as well as innovative in the field aforesaid.